Spatial Models of Travel Behavior and Land Use Restriction. Issue 1 (31st December 2023) - Mueller, Andrew G.; Weiler, Stephan
Abstract: This paper develops a spatial econometric model of transportation mode choice and tests the association between zoning and other built environment variables and the choice of auto and non-auto transportation. We provide an extensive review of spatial econometrics and demonstrate the importance of using models that treat space formally when investigating urban transportation behavior. Using a unique combination of travel, employment, and built environment datasets from Denver, Colorado, we confirm previous results that built environment variables have a small association with choice of transportation mode and show the benefits of formal spatial modeling to the traditional probit model.